Benign tumors in gynecology and obstetrics. Benign tumors of the uterus. - Serrepe Ascencio, Juan (2015)
200 cases of uterine fibroleiomioma treated at the Gynecology Service of the North Central Hospital of the IPSS, between January 1975 to March 1981. We studied the variability of their behavior is tested in terms of size, number, anatomical location and production symptoms. It is considered that race is not a predisposing factor in "our environment. Its most common presentation was in the second half of the menstrual life and symptoms were independent of the size of the fibroids, vaginal bleeding being the predominant symptom. Concur in the diagnosis and guidance therapy, radiology and ultrasound. The treatment is essentially surgical and according to the importance of reproductive function of each patient, a myomectomy or hysterectomy will be chosen. The postoperative complications are rare, predominantly infections. malignant degeneration was found in 0.5% and other malignancies in association with 1%.